2021
DOI: 10.47836/ifrj.28.6.13
|View full text |Cite
|
Sign up to set email alerts
|

The infusion of goji berries and red dates ameliorates the overall qualities of kenaf leaves tea

Abstract: Kenaf (Hibiscus cannabinus) is an industrial crop in Malaysia, and especially used as a source for composite wood. Kenaf leaves as a by-product of the plantation can be consumed as food due to its high nutritional value. Kenaf leaves have high antioxidant properties, thus are suitable to be made into herbal tea. However, its flavour is considered sour, thus presenting a challenge for product development. The main objective of the present work was to evaluate the physicochemical and functional (ascorbic acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The study proposed that the reported radical scavenging activities are highly attributed to the total phenolic content and polysaccharide content of the extract. Other studies also reported likewise [11,12,34].…”
Section: Leaf Extractmentioning
confidence: 68%
See 3 more Smart Citations
“…The study proposed that the reported radical scavenging activities are highly attributed to the total phenolic content and polysaccharide content of the extract. Other studies also reported likewise [11,12,34].…”
Section: Leaf Extractmentioning
confidence: 68%
“…Moreover, the kenaf leaves can also be processed into tea that has functional values such as anti-diabetic properties. According to Goh, et al [11], the infusion of kenaf leaf tea with goji berries and red date tea (6:4) managed to exhibit hypoglycaemic effects by inhibiting the activity of the α-amylase enzyme. The study proposed that the mixture of both teas can work synergistically to disrupt the α-amylase enzyme, which plays a role in carbohydrate (starch, and glycogen) digestion (Figure 9).…”
Section: Leaf Extractmentioning
confidence: 99%
See 2 more Smart Citations